PENGARUH MEDITASI TERHADAP TEKANAN DARAH PADA ORANG HIPERTENSI - Marthayoga, Bagus Adi (Coping: Community of Publishing in Nursing, 2015)
Hypertension is a core problem that can cause of death for non-infection category disease. Besides that, hypertension also is a major cause of heart failure and stroke. One of hypertension causes is the increase stimulation of sympatic neuron stress response excessively. Meditation is a manner to reduce stress response with relaxation technique. This research aim to find out the influence of meditation for  the  blood pressure people’s with hypertension in bungbungan-banjarangkan-klungkung. This research using quasy experience ( pretest-posttest ) design on 20 respondents that chosen by purposive sampling technique, and it divided into a control group and intervention group. Based on the results of paired t-test ( p < 0.05 ) on intervention group obtained 0,022systole and 0,047diastole blood pressure, it means there is a difference blood pressure on intervention group after given meditation, however, on control group the systole and diastole are 0.47 , 0,216 it means there is not difference blood pressure on control group. Analysis the differences in blood pressure on both of the group using independent t-test ( p < 0.05 ) with the value 0,088 on the systole and 0,194 for the diastole, that means there is no difference blood pressure in the systole and diastole of control and intervention group.
Keywords: blood pressure; hypertension; meditation